2021
DOI: 10.3390/biomedicines9111614
|View full text |Cite
|
Sign up to set email alerts
|

An Epigenetic Insight into NLRP3 Inflammasome Activation in Inflammation-Related Processes

Abstract: Aberrant NLRP3 (NOD-, LRR-, and pyrin domain-containing protein 3) inflammasome activation in innate immune cells, triggered by diverse cellular danger signals, leads to the production of inflammatory cytokines (IL-1β and IL-18) and cell death by pyroptosis. These processes are involved in the pathogenesis of a wide range of diseases such as autoimmune, neurodegenerative, renal, metabolic, vascular diseases and cancer, and during physiological processes such as aging. Epigenetic dynamics mediated by changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 139 publications
(169 reference statements)
0
19
0
Order By: Relevance
“…Inflammasome activation is associated with rapid innate inflammatory response and leads mainly to the production of IL-1β and IL-18 [ 55 , 56 ]. The inflammation process that is triggered by the inflammasome contributes to the pathogenesis of a wide spectrum of chronic diseases, including obesity [ 51 , 57 ].…”
Section: Mechanisms Explaining the Association Between Gut Microbiota...mentioning
confidence: 99%
“…Inflammasome activation is associated with rapid innate inflammatory response and leads mainly to the production of IL-1β and IL-18 [ 55 , 56 ]. The inflammation process that is triggered by the inflammasome contributes to the pathogenesis of a wide spectrum of chronic diseases, including obesity [ 51 , 57 ].…”
Section: Mechanisms Explaining the Association Between Gut Microbiota...mentioning
confidence: 99%
“…By contrast, extrinsic and intrinsic apoptosis activate pannexin-1 to drive NLRP3 inflammasome assembly [ 136 ], and caspase-1 initiates apoptosis in the absence of gasdermin D [ 137 ]. Finally, note that epigenetic dynamics is a key regulator of the expression of inflammasome components and its further activation [ 138 ]. Therefore, targeting mitochondrial maintenance may control cell homeostasis, and in turn, delay aging and prevent related diseases such as RA.…”
Section: Interplay Between Mitochondrial Oxidative Stress Metabolic S...mentioning
confidence: 99%
“…In fact, the key drivers of RA synovitis, TNF and IL-1, reprogram the epigenomic landscape of FLS by altering chromatin and contributing then to induce unremitting expression of arthritogenic genes in RA synoviocytes [ 233 , 234 , 235 ]. Additionally, note as different epigenetic changes are involved into NLRP3 inflammasome activation [ 138 ]. Histone modification and micro-RNA are too involved in epigenetic regulation in the pathogenesis of RA.…”
Section: Interplay Between Mitochondrial and Epigenetic Mechanisms In Ramentioning
confidence: 99%
“…The inflammasome is a key player in activating caspase-1 and stimulating the inflammatory cytokines interleukin IL-1β and IL-18 [ 44 ]. The trigger of inflammasomes starts when immune cells face pathogen-associated molecular patterns (PAMPs) or danger-associated molecular patterns (DAMPs) by pattern recognition receptors (PRRs) [ 45 ]. During recent years, it was demonstrated that NLRC4, caspase-1, ASC and IL-18 are elevated in the aged brain, confirming its key role in the innate immune response [ 46 , 47 ].…”
Section: Cytokines and Neuroinflammationmentioning
confidence: 99%